The Effectiveness of The Pension Fund Disbursement System Through the Taspen Authentication Application in Taspen Cipondoh Branch - Amalia Hermayati; Listyaningsih; Ipah Ema Jumiati (International Journal of Social Sciences Review, 2022)
The background of this research was focused on the problems in the taspen authentication application system such as system errors, lack of system updates, lack of availability of Human Resources for TASPEN Cipondoh employees, and the number of queues that are still piling up at the beginning of the month. The purpose of this study is to find out how the pension funds disbursement system through the taspen authentication application at PT. TASPEN Cipondoh Branch. The theories used by the theory of program effectiveness according to Duncan in steers (2012: 53) include: Aspects of Goal Achievement, Aspects of Integration, and Aspects of Adaptation. This research uses qualitative methods. The results of the taspen authentication application research there are system problems that often occur such as system errors, unstable networks, and application socialization processes that have not been maximized. The low competence level of officers in providing services so that in terms of its use retirees still do not feel the ease of the Taspen Authentication application. The suggestion submitted by the researcher is PT. TASPEN is improving the taspen authentication application system, improving information publication by conducting gradual socialization and training directly to retirees related to the use of the taspen authentication application, as well as improving the competence of officers by providing special training in the field of information technology.